Evaluating the response of neoadjuvant chemotherapy for treatment of breast cancer: are tumor biomarkers and dynamic contrast enhanced MR images useful predictive tools? - Zhang, Zijing; Zhang, Wei; Jin, Yiting; Wang, Hongying; Gu, Fei; Zhou, Jian; Lao, Zhengyin; Xu, Zude; Tang, Feng; Zou, Liping; Tang, Weijun; Lu, Rong; et al. (Journal of Thoracic Disease, 2014)
Objective: In order to evaluate the therapeutic response to neoadjuvant chemotherapy (NAC) for breast cancer, this research focused on the changes in expression of tumor biomarkers and the correlations associated with changes of magnetic resonance imaging (MRI) pre- and post-NAC. We also compared the accuracy of MRI and pathology in terms of residual tumor extent after NAC. Methods: MRI was performed before and after four courses of cyclophosphamide, epirubicin and paclitaxel (CET) NAC on 114 patients treated in Huashan Hospital (Fudan University) from December 2009 to January 2013. All patients were pathologically diagnosed with invasive breast cancer via core needle biopsy. A series of tumor biomarkers, including P-glycoprotein (P-gp) and Ki-67, was tested by immunohistochemistry in both core needle biopsy and surgical specimens. The changes in tumor biomarker expression and the shrinkage of tumor on MRI were observed. The residual tumor extent after NAC was compared in terms of MRI and histopathology, and the accuracy of MRI was evaluated by both residual tumor extent and by NAC therapeutic effect. Together, these methods enabled a prognostic estimate of NAC. Results: The P-gp expression before NAC was used to evaluate the therapeutic effect of NAC. The upregulation of P-gp expression after NAC was associated with poor therapeutic effect (P=0.0011). The expression of Ki-67 was significantly down-regulated (P